In Vitro Activities of Posaconazole (Sch 56592) Compared with Those of Itraconazole and Fluconazole against 3,685 Clinical Isolates of Candida spp. and Cryptococcus neoformans - Pfaller, M. A. (American Society for Microbiology, 2001)
Posaconazole is a new investigational triazole with broad-spectrum antifungal activity. The in vitro activities of posaconazole were compared with those of itraconazole and fluconazole against 3,685 isolates of Candida spp. (3,312 isolates) and C. neoformans (373 isolates) obtained from over 70 different medical centers worldwide. The MICs of the antifungal drugs were determined by broth microdilution tests performed according to the National Committee for Clinical Laboratory Standards method using RPMI 1640 as the test medium. Posaconazole was very active against all Candida spp. (MIC at which 90% of the isolates were inhibited [MIC(90)], 0.5 μg/ml; 97% of MICs were ≤1 μg/ml) and C. neoformans (MIC(90), 0.5 μg/ml; 100% of MICs were ≤1 μg/ml). Candida albicans was the most susceptible species of Candida (MIC(90), 0.06 μg/ml), and Candida glabrata was the least susceptible (MIC(90), 4 μg/ml). Posaconazole was more active than itraconazole and fluconazole against all Candida spp. and C. neoformans. These results provide further evidence for the spectrum and potency of posaconazole against a large and geographically diverse collection of clinically important fungal pathogens.